The Performance of Sharia Banks Employees X Branch Batam Through Work Motivation - Sri Langgeng Ratnasari; Gandhi Sutjahjo; Dewi Yana (ETIKONOMI, 2019)
There are several affecting factors to the Employees' performance. This research aimed to examines the factor that influences work motivation and employees' performance. The method was the structural equation model. The results found that leadership style and compensation affect the work motivation, but the variable of work discipline does not have an impact on work motivation. This study also found that work discipline and compensation affect the employees' performance, but the leadership style does not have an impact. The Policy implications suggest the chairman to set-up leadership style appropriate to the employees' situation, and compensation should be enhanced, awards and penalties apply to increase employees'discipline and welfare.JEL Classification: G21, M12